The epidemiology and medical care costs of Echinococcus granulosusis in Jahrom, southern Iran from 2007 to 2017 - Hadi Khatonaki (Taylor & Francis Group, 2020)
Background: Echinococcus granulosus is a rare parasitic infection causing Cystic Echinococcosis, which can be dangerous due to involving the body. This parasitic infection is a significant health problem in Iran. However, little is known about this disease, specifically in Jahrom city; thus, we aimed to investigate the epidemiology and the economic impact of the illness. Methods: In this descriptive cross-sectional study, the files of 137 patients who were under the care, and treatment of the final diagnosis of Cystic Echinococcosis were evaluated by reviewing the information such as age, gender, occupation, place of residence was collected, and analyzed. Results: Human cystic echinococcosis cases were more common in females, 57.2% (12 patients) and 42.8% (9 patients) were male. In terms of age, most patients (23.8%) were in the age range from 21 to 30 years. The chief complaint at diagnosis, in all cases, was abdominal pain. Besides, 71.42% of the cases had the liver involvement alone, 9.52% had the lung involvement alone, 9.52% had a co-infection of liver and lung, and 4.74% had the kidney involvement alone. Conclusions: The results of the present study are beneficial in determining the disease status and the epidemiology of hydatid cyst in this area.